Review and Potential Analysis of R1234yf Heat Pump Technology - Liu Yusheng; Li Wanyong; Shi Junye; Chen Jiangping (Zhileng xuebao)
Electric vehicles do not have sufficient engine waste heat to meet heating demands in winter. As such, heat pump technology has become a research hotspot to achieve a higher efficiency than electric resistance heat. To meet the gradual and stringent environmental regulations, there have been many studies on the replacement of vehicle heat pump system refrigerants. This paper reviews the research on R1234yf heat pump technology in recent years. As one of the popular alternative refrigerants for R134a, R1234yf has a global warming potential (GWP) of less than 1 and physical properties very similar to R134a.The properties of R1234yf are in line with the work requirements of vehicle heat pump systems. The system operation characteristics and performance are also very similar to R134a. In terms of heat transfer, the boiling heat transfer performance of R1234yf is slightly better than that of R134a. The condensation heat transfer coefficient is different in the research conclusions of various scholars, but the pressure drop in the condensation process of R1234yf is 5%–10% lower than that of R134a, which benefits the performance improvement. In the simulation and experimental research of many R1234yf and R134a systems, the performance of R1234yf heat pump is similar to R134a, but it can surpass R134a by optimizing components, economized vapor injection (EVI), and improving working conditions. R1234yf’s saturation pressure at a low saturation temperature is approximately15% higher than R134a and can adapt to higher compressor speeds. Therefore, it has a better heating performance at low temperatures than R134a;its lower compressor discharge temperature makes the system work more stable. The relative improvement using EVI is also better for R1234yf than for R134a.Therefore, R1234yf has a better working performance and prospects for vehicle heat pumps and can, therefore, be used as an alternative refrigerant for R134a.